The Development of teaching materials in the 3D Page Flip-based Indonesian Literature History course for students of the Indonesian Education Study Program - Sri Listiana Izar (Edumaspul: Jurnal Pendidikan, 2023)
This research focuses on developing teaching materials in the 3d Page flip-based Indonesian literary history course. This research uses a 4D development model (define, design, develop, and disseminate). The objectives of this study are 1) to determine how the validity of the development of teaching materials in the 3d Page flip-based Indonesian literature history course at FKIP UMSU, and 2) how effective the development of 3d Page flip-based Indonesian literature history teaching materials at FKIP UMSU. This research produced teaching materials for Indonesian literary history based on 3d Page flip. The results of the study were validated by expert experts. The results of the validation of teaching materials are calculated using the average for each validation indicator. While the effectiveness of teaching materials, student responses in the Indonesian literary history course are based on 3d page flip after being given teaching materials in the learning process. This research was conducted at the Education Study Program Indonesian the Faculty of Teacher Training and Education UMSU which was conducted in 2021. In this research, teaching materials have been developed in the 3d Page flip-based Indonesian literary history course.